Lantus, the first peakless basal insulin analogue: 10 years of clinical experience in children and adolescents - Tamara Leonidovna Kuraeva (Сахарный диабет)
This review analyses existing literature, including authors' own data, describing the results of clinical trials which assess safety and efficacy of insulin Glargine (Lantus?) in children and adolescents, as well as peculiar features of T1D management in this age group, including the challenge of reducing the rate of hypoglycemia while maintaining adequate glycemic control. The article also discusses various issues in T1D management in children and adolescents, including the role of glycemic control in development of vascular complications, hypoglycemia and the variability of glycemia. The data confirm the high efficacy of Lantus insulin in respect to metabolic control, including the decrease in the incidence of hypoglycemia and in variability of glycemic profile, the safety of its clinical use in treatment of children, including young children, and adolescents, as well as its ability to improve the quality of life for patients and their parents.